Current Studies in Social Sciences VI - Çitil Akyol, Canan; Yıldırım, Taşkın; Kar, Tuğçem; Serttaş, Fatma Özgü; Kütükçü, Murat; Öçal, Bora; Dikmen, Çiğdem Belgin; Kuloğlu, Ayhan; Dursun, Erdal (Academician Publishing Book DOI Portal, 2023)
-